2013
DOI: 10.1007/s11936-013-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Therapy for Claudication: Latest Advances

Abstract: Opinion statement Peripheral artery disease (PAD) creates a significant national and international healthcare burden. A first line treatment for PAD is supervised walking exercise in hospitals and clinics. Specifically, supervised walking exercise seeks to improve the classic symptom associated with PAD, intermittent claudication (IC), which is characterized by cramping, aching and pain of the muscles in the lower extremities during walking. While effective, supervised walking exercise is often not prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…The usual care approach, have a trend to deteriorate walking performance, considering that PAD is a progressive atherosclerotic disorder that deteriorates over time. These findings are in agreement with several randomized controlled trials and systematic reviews that compared supervised walking exercise to unsupervised exercise and usual care programs (McDermott et al, 2009;Hamburg and Balady, 2011;Vascular Disease Foundation, 2012;Mays and Regensteiner, 2013;McDermott, 2013;Lane et al, 2017).…”
Section: Combined Exercise Vs Usual Care Approachsupporting
confidence: 89%
See 1 more Smart Citation
“…The usual care approach, have a trend to deteriorate walking performance, considering that PAD is a progressive atherosclerotic disorder that deteriorates over time. These findings are in agreement with several randomized controlled trials and systematic reviews that compared supervised walking exercise to unsupervised exercise and usual care programs (McDermott et al, 2009;Hamburg and Balady, 2011;Vascular Disease Foundation, 2012;Mays and Regensteiner, 2013;McDermott, 2013;Lane et al, 2017).…”
Section: Combined Exercise Vs Usual Care Approachsupporting
confidence: 89%
“…Thereby, the promotion of exercise training in patients with PAD and IC is an important non-pharmacological strategy to treat and prevent this disease, which provides favorable systemic vascular effects that may reduce cardiovascular events and improve blood perfusion in PAD (McDermott et al, 2009). Supervised exercise programs have a higher efficacy in improving the physical fitness in particular the walking performance (i.e., claudication onset distance [COD], absolute claudication distance [ACD] or maximal walking distance [MWD]) and the symptomatology of this disease when compared to unsupervised exercise programs (McDermott et al, 2009;Mays and Regensteiner, 2013;McDermott, 2013). However, a recent meta-analysis found that structured home-based exercise programs are effective at improving walking performance in patients with PAD (Golledge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that a session includes three series of 8–12 repetitions of each exercise for each lower limb muscle group. A recess between the series of exercises should be 1-2 minutes [1, 7, 23, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Given its low-cost and proven effectiveness, physiotherapy for cardiovascular health and/or claudication is essential at the first-level hospital. 46 …”
Section: Resultsmentioning
confidence: 99%